SUPERVISI AKADEMIK DALAM MENINGKATKAN PROFESIONALITAS GURU BK - Nur Ajizah Panjaitan; Nurhaliza; Gusman Lesmana (Nirta Learning Centre, 2026)
This study aims to analyze the role of academic supervision in improving the professionalism of Guidance and Counseling (BK) teachers. Academic supervision is a strategic effort in developing the professional competence of BK teachers in schools. The research method used was a literature review, analyzing various sources related to academic supervision and the professionalism of BK teachers from 2017 to 2025. The results indicate that academic supervision, implemented systematically, planned, and continuously, can improve the pedagogical, professional, personal, and social competence of BK teachers. Effective academic supervision includes planning, implementation, evaluation, and follow-up, involving collaboration between supervisors and BK teachers. Good implementation of academic supervision will impact the quality of guidance and counseling services to students. The conclusion of this study confirms that academic supervision is an important instrument in improving the professionalism of BK teachers through continuous coaching, guidance, and competency development. Keywords: Academic Supervision, Guidance and Counseling, Professional Competence , Teacher Professionalism.